GDP Per Capita Impact on Infant Mortality Rate: Southeast-Asia Lower Middle-Income Countries 2005-2019 - Bramantyo, Kenang Gusti; Sihaloho, Estro Dariatno (MediaTrend, 2025)
Infant mortality Rate (IMR) is one of the main indicator of the socioeconomic development and the health status of a country. Despite how significant the impact of reducing the infant mortality rate to a country, countries in Southeast Asia, especially the lower middle-income few, still have a relatively high number of Infant mortality rate. Studies have been conducted on the impact of few variables that determine the number of Infant mortality rate. In this paper, the aim is to analyse a few socioeconomic variables such as GDP per Capita, health care expenditure as a share of GDP, total fertility rate and female participation in the labour force on infant mortality rate of lower middle-income countries in Southeast Asia. This study found that GDP per Capita and health care expenditure as a share of GDP have a significant and negative impact on infant mortality rate during the study period. While as Total fertility rate have a significant and positive impact on infant mortality rate, and there is no significant effect of female labour force participation rate on infant mortality rate in the studied countries during the study period.